Antibacterial Activity of Etanol Extract of Pinang (Areca catechu L.) Clup against Streptococcus mutans and Porphyromonas gingivalis - Nuryanti, Siska; Herwin, Herwin; Rahmayanti, Hani Rahmayanti (Fakultas Farmasi, Universitas Muslim Indonesia, 2025)
Areca nut (Areca catechu L.) is a plant that has many uses and can be used for traditional medicine. Areca nut skin can be used to treat indigestion (dyspepsia), edema and beriberi due to low urine output. This study aims to determine the antibacterial activity of ethanol extract of areca nut peel against the test bacteria Streptococcus mutans and Porphyromonas gingivalis. In this research, the areca nut peel simplicia was extracted using the maceration method with 96% ethanol solvent, after which a liquid ethanol extract was obtained and then evaporated using a rotary vacuum evaporator to obtain a thick extract. After the extract is thick, a Minimum Inhibitor Concentration (MIC) test and a Minimum Bactericide Concentration (MBC) test are carried out. The results obtained in the Minimum Inhibitor Concentration (MIC) test and Minimum Bactericide Concentration (MBC) test on Streptococcus mutans and Porphyromonas gingivalis bacteria were 0.5%. Antibacterial activity test using the agar diffusion method was obtained, for Streptococcus mutans bacteria, the largest inhibitory zone diameter at a concentration of 16% was 12.58 mm and for Porphyromonas gingivalis bacteria at a concentration of 16%, namely 10.93 mm. Based on research, ethanol extract of areca nut peel has antibacterial potential.